Campaign Model Of Conservative Islamic Parties In Perspectivefiqh Siyasah Al-Mawardiy - Hawari, Nadirsah; Agustamsyah, Agustamsyah; Artalim, Muntaha (JURNAL TAPIS, 2024)
Legislative elections returned to the people of Lampung in 2019 with more participants than the previous election. For parties participating in the polls, especially Islamic parties, this is an event for contestation, competition, and at the same time a gamble on existence, considering that several parties have disappeared under the parliamentary threshold and have to work hard to return to the political scene. Party elites implemented various methods and strategies to win the hearts of prospective voters, ranging from the most substantive educational to the most narrative pragmatic. The simultaneous implementation of presidential and legislative elections is a special moment and a golden opportunity for political parties to gain votes and seats. However, which party has the most effective and successful strategy in increasing its electoral politics? This research is a field study using interviews, observation, and documentation techniques which are analyzed using content analytic methods. This study found that conservative Islamic parties such as PPP, PKB, and PBB had a special strategy for winning the elections at that time, however, of the three existing Islamic parties, only PKB managed to increase the number of seats obtained sufficiently for the total number of assembly members in Lampung. The research also found that the three conservative parties uphold political values in Imam Mawardi's Fiqh Siyasah theory.